2022
DOI: 10.3390/agriculture12101518
|View full text |Cite
|
Sign up to set email alerts
|

What If the World Went Vegan? A Review of the Impact on Natural Resources, Climate Change, and Economies

Abstract: Contemporary knowledge on climate change has given rise to a group of advocates who suggest global veganism as an adaptive means of mitigating the threat of climate change. Livestock farming is accused of contributing massively to greenhouse gas (GHG) emissions. Some studies suggest that eliminating meat from the diet (i.e., moving to a vegan diet) can reduce GHG emissions globally, while other studies suggest that livestock farming may make a smaller contribution to GHG emissions compared to previous estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…There is a slight global increase in the number of vegetarians and vegans, driven by various factors such as health concerns, climate change, and animal welfare considerations. (Dorgbetor et al, 2022). However, traditional rural diets often rely heavily on animal products, which may not align with the dietary preferences of tourists who follow vegan or vegetarian diets.…”
Section: Can Innovative Gastronomy Contribute To Achieving Sustainabl...mentioning
confidence: 99%
“…There is a slight global increase in the number of vegetarians and vegans, driven by various factors such as health concerns, climate change, and animal welfare considerations. (Dorgbetor et al, 2022). However, traditional rural diets often rely heavily on animal products, which may not align with the dietary preferences of tourists who follow vegan or vegetarian diets.…”
Section: Can Innovative Gastronomy Contribute To Achieving Sustainabl...mentioning
confidence: 99%
“…Besides many animal rights and animal welfare issues, diet has a major impact on both the individual’s ecologic footprint and health. There is substantial evidence supporting the fact that animal products and animal-based foods have a negative impact on the environment, and this evidence includes, for example, the related increased emission of greenhouse gasses (e.g., Notarnicola et al, 2017 ; Chai et al, 2019 ; Rabès et al, 2020 ; Allenden et al, 2022 ; Filippin et al, 2023 ; McDougall, 2023 ; Scarborough et al, 2023 ; see, however, also Rosi et al, 2017 ; Vettori et al, 2021 ; Dorgbetor et al, 2022 ). Similarly, vegan diets are associated with potential health benefits (e.g., Wirnitzer, 2020 ; Selinger et al, 2022 ; McDougall, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this implies the rearing of animals and cultivation of crops. Farmers obtain benefits from this system as some animals are used in land preparation, serve as insurance against crop failure [3] and their droppings are a source of soil amendment especially at the onset of the rainy season. In fact, a study by Herve and others [4] in 2016 indicated, 31% of farmers in Northern Region (not to be confused with northern Ghana) amend their soils using organic manure sources varying from animal droppings, crop residue and compost.…”
Section: Introductionmentioning
confidence: 99%